THEORETICAL FOUNDATIONS OF VARIATIONIST SOCIOLINGUISTICS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines how linguistic diversity is distributed across society. It explores the evolution of variationist sociolinguistics, from Georg Wenker’s early maps to William Labov’s empirical research. By analyzing factors like social class, age, and gender, the study indicates that language change is systematically tied to social structure. Specifically, it highlights how /r/ pronunciation reflects social prestige within speech communities. Ultimately, the research demonstrates that language is a dynamic social phenomenon rather than a static entity.
Keywords: variationist sociolinguistics, social stratification, speech communities, linguistic variation, William Labov.